Timing-synchronization analysis for IEEE 802.11a wireless LANs in frequency-nonselective Rician fading environments. - Kun-Wah Yip
This paper derives and computes the probability of synchronization failure Pfail for IEEE 802.11a wireless LANs on frequency-flat Rician fading channels. For a frequency offset within ±232 kHz, it is shown that its effect on the synchronization performance is minor. The Eds/N0 ratios required to achieve Pfail=10-3 and 10-4 are computed, where Eds is the data-symbol energy. We find that Eds/N0 ratios over 20 dB are generally required for channels with Rician factors K≤6 dB. In particular, Eds/N0 ratios that yield Pfail=10-4 exceed 30 dB for K≤4 dB.
Keywords: IEEE 802.11a.; Frequency-flat Rician fading channels; Frequency-nonselective channel; Orthogonal frequency division multiplexing; Sliding correlator; Synchronization failure probability; Timing synchronization analysis; Wireless LANs; Wireless local area networks